Stem Cells, Cell Therapies, and Bioengineering in Lung Biology and Disease 2019. Issue 4 (19th October 2020) - Wagner, Darcy E.; Ikonomou, Laertis; Gilpin, Sarah E.; Magin, Chelsea M.; Cruz, Fernanda; Greaney, Allison; Magnusson, Mattias; Chen, Ya-Wen; Davis, Brian; Vanuytsel, Kim; Rolandsson Enes, Sara; Krasnodembskaya, Anna; et al.
A workshop entitled "Stem Cells, Cell Therapies and Bioengineering in Lung Biology and Diseases" was hosted by the University of Vermont Larner College of Medicine in collaboration with the National Heart, Lung and Blood Institute, the Alpha-1 Foundation, the Cystic Fibrosis Foundation, the International Society for Cell and Gene Therapy and the Pulmonary Fibrosis Foundation. The event was held from July 15 to 18, 2019 at the University of Vermont, Burlington, Vermont. The objectives of the conference were to review and discuss the current status of the following active areas of research: 1) technological advancements in the analysis and visualisation of lung stem and progenitor cells; 2) evaluation of lung stem and progenitor cells in the context of their interactions with the niche; 3) progress toward the application and delivery of stem and progenitor cells for the treatment of lung diseases such as cystic fibrosis; 4) progress in induced pluripotent stem cell models and application for disease modelling; and 5) the emerging roles of cell therapy and extracellular vesicles in immunomodulation of the lung. This selection of topics represents some of the most dynamic research areas in which incredible progress continues to be made. The workshop also included active discussion on the regulation and commercialisation of regenerative medicine products and concluded with an open discussion to set priorities and recommendations for future research directions in basic and translation lung biology. This workshop report discusses recent advances in cell therapy and bioengineering approaches for repair and regeneration of diseased lungs https://bit.ly/2DqA8eu